Penatalaksaan Fisioterapi Pada Kasus Bells Palsy Sinistra di Rsu Aisyiyah Ponorogo - Putri, Fani Karisma, Agus Widodo, S.Fis, M.Kes (2016)
Background: Bell's palsy is a disorder of the face caused by the paralysis of the facial nerve that occurs acutely, and the cause is idiopathic (unknown) that can cause facial muscle weakness and decreased functional activity of the face. In such cases can be dealt with physiotherapy odalities. Physiotherapy in these cases can improve facial muscle strength and improve functional activities face with modalities: infrared, electrical stimulation, massage, and mirror excercise Objective: To determine the physiotherapy management in cases of Bell's palsy in improving facial muscle strength, and improve functional activities face with modalities: Infrared, Electrical Stimulation, Massage and Mirror Excercise Results: After physiotherapy for 7 times, showed the number of functional activities face T0: 3 to T7: 30. Some of the facial muscles increases muscle strength among the frontal muscle T0: 0 become T6: 1, Muscle corugator supercili T0: 0 become T6: 1, muscle procerus T0: 0 become T6: 1, muscle nasal T0: 0 become T6: 1, muscle zigomaticum major T0: 0 become T6: 1, muscle zigomaticum minor T0: 0 become T6: 1, orbicularis oculi muscle T0: 0 become T6:1, platysma muscle T0: 3 become T6: 5. Conclusion: Giving infrared, electrical stimulation, massage and mirror excercise face can increase muscle strength and improve facial functional activity in patients with Bell's palsy.